2014
DOI: 10.1186/1476-4598-13-207
|View full text |Cite
|
Sign up to set email alerts
|

Twist1 expression induced by sunitinib accelerates tumor cell vasculogenic mimicry by increasing the population of CD133+ cells in triple-negative breast cancer

Abstract: BackgroundHypoxia induced by antiangiogenic agents is linked to the generation of cancer stem cells (CSCs) and treatment failure through unknown mechanisms. The generation of endothelial cell-independent microcirculation in malignant tumors is defined as tumor cell vasculogenic mimicry (VM). In the present study, we analyzed the effects of an antiangiogenic agent on VM in triple-negative breast cancer (TNBC).MethodsMicrocirculation patterns were detected in patients with TNBC and non-TNBC. Tientsin Albino 2 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 46 publications
3
123
0
Order By: Relevance
“…15,24 Moreover, targeting VEGF, VEGF receptors or endothelial cells shows limited effectiveness on VM formed by tumor cells. 25 Previously, we found there is increased VM in TNBC compared within non-TNBC. Based on previous studies, we hypothesize that the VM channels in TNBC are responsible for the tumor rebound and treatment failure of anti-angiogenic agents.…”
Section: Introductionmentioning
confidence: 79%
“…15,24 Moreover, targeting VEGF, VEGF receptors or endothelial cells shows limited effectiveness on VM formed by tumor cells. 25 Previously, we found there is increased VM in TNBC compared within non-TNBC. Based on previous studies, we hypothesize that the VM channels in TNBC are responsible for the tumor rebound and treatment failure of anti-angiogenic agents.…”
Section: Introductionmentioning
confidence: 79%
“…Twist is capable to open nuclear membrane pores with the help of an accessory protein and enters the nucleus to regulate transcription of downstream genes that are involved in the process of VM [38]. However, Twist2 share several of similar functions including their regulation of haematological malignancies and their role in cancer progression and metastasis with Twist1 [39][40][41]. Studies found that Twist1 and Twist2 were both up-regulated in metastasis-associated colon cancer.…”
Section: Twist1/bmi1mentioning
confidence: 99%
“…VM is associated with increased tumor aggressive biology and tumorrelated patient mortality. The channel of VM consists of plasticity of tumor cells in the external wall, remodeling of the extracellular matrix (ECM) on the inner wall, and connection to the host microcirculation system (Sun et al, 2011;Yao et al, 2013;Zhang et al, 2014) with genetically dysregulated tumor cells having a pluripotent embryoniclike gene type (Hendrix et al, 2003), suggesting the participation of CSCs. We and others have demonstrated that vascular niche may regulate CSCs fate (Hilbe et al, 2004;EI Hallani et al, 2010; and promote metastasis through the down-regulation of E-cadherin.…”
Section: Introductionmentioning
confidence: 99%